2006
DOI: 10.4049/jimmunol.177.4.2621
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 Plays an Essential Role in Chronic Allergic Inflammation of the Skin via CRTH2 Receptor

Abstract: PGD2 plays roles in allergic inflammation via specific receptors, the PGD receptor designated DP and CRTH2 (chemoattractant receptor homologous molecule expressed on Th2 cells). We generated mutant mice carrying a targeted disruption of the CRTH2 gene to investigate the functional roles of CRTH2 in cutaneous inflammatory responses. CRTH2-deficent mice were fertile and grew normally. Ear-swelling responses induced by hapten-specific IgE were less pronounced in mutant mice, giving 35–55% of the responses of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
166
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(185 citation statements)
references
References 36 publications
15
166
0
1
Order By: Relevance
“…These data are generally consistent with the results of our metabolism studies. PGD 2 and its receptors, DP and CRTH2, are known to be involved in chronic allergic skin inflammation (Angeli et al, 2004;Satoh et al, 2006). The marked increases in PGFS and PGIS that we noted in response to UVB also suggest that eicosanoids produced by these enzymes may be important mediators of cutaneous inflammation (Muller et al, 2000;Takahashi et al, 2002).…”
Section: Discussionmentioning
confidence: 62%
“…These data are generally consistent with the results of our metabolism studies. PGD 2 and its receptors, DP and CRTH2, are known to be involved in chronic allergic skin inflammation (Angeli et al, 2004;Satoh et al, 2006). The marked increases in PGFS and PGIS that we noted in response to UVB also suggest that eicosanoids produced by these enzymes may be important mediators of cutaneous inflammation (Muller et al, 2000;Takahashi et al, 2002).…”
Section: Discussionmentioning
confidence: 62%
“…8 Transgenic mice overexpressing human PGD synthase showed exacerbation of ovalbumin (OVA)-induced lung inflammation associated with pronounced eosinophilia and increased Th2 cytokine production. 9 In our previous studies, mice deficient in the CRTH2 gene were characterized by alleviated IgE-mediated cutaneous responses, contact hypersensitivity reactions, 10 and cedar pollen dermatitis. 11 However, PGE2 is produced by a variety of cells, including fibroblasts and macrophages, and exerts its effects via prostaglandin E2 (EP)1, EP2, EP3, and EP4 receptors.…”
mentioning
confidence: 99%
“…SPF/VAF male CRTH2-deficient (BALB/c) mice (31) were bred in the Keio University Animal Research Facility. All animals were housed at the facility in bioBubble barrier units under positive pressure.…”
Section: Animalsmentioning
confidence: 99%
“…CRTH2, another PGD 2 receptor identified as a molecule preferentially expressed on Th2 lymphocytes, eosinophils, and basophils, transduces the chemokinetic activity of PGD 2 on eosinophils (26,27). We and others have recently shown that CRTH2 agonists administered into the trachea led to translocation of eosinophils from the bloodstream into the airway (28 -30), and that CRTH2-deficient mice exhibited decreased infiltration of eosinophils and other inflammatory cells during chronic allergic skin inflammation (31).…”
mentioning
confidence: 99%